Suppression of monocyte and neutrophil function by recombinant IL-2 - Susan E. Smith; Gayle D. Warren; Yee-Hing Thong; Joe G. McCormack (Mediators of Inflammation)
Little IS known about the influence of IL-2 on phagocytes. We now describe the effects of human recombinant IL-2 on human neutrophil and monocyte functions related to mobility, phagocytosis, glucose uptake, respiration and degranulation. Neutrophil adherence and hexose monophosphate shunt activities were both suppressed after incubation with IL-2. IL-2 had no effect on neutrophil migration, phagocytosis, deoxyglucose uptake or degranulation, ionocytes demonstrated a greater sensitivity to IL-2 with suppression of monocyte adherence, random and stimulated migration, glucose uptake and hexose monophosphate shunt activity, even after addition of phorbol myristate acetate. Monocyte phagocytosis and degranulation were not affected. All of the effects observed were dose-dependent within a biologically active range for IL-2. These studies suggest that IL-2 may have an important down-regulatory role across a broad range of monocyte functions including movement, deoxyglucose uptake and respiration. However, its role in regulation of neutrophil function is limited to adherence and respiration. IL-2 may be a more versatile cytokine than has previously been appreciated.